THE INFLUENCE OF BRAND IMAGE, PRICE AND PROMOTION ON BRAND SWITCHING (Survey on Student of Business Administration Faculty of Administrative Science Brawijaya University Who Had Ever Switched to Other SIM Card Providers) - Adi Cahyono (Jurnal Administrasi Bisnis, 2015)
This study aimed to understanding the simultaneously influences of the brand image, price and promotion on brand switching. Understanding the influence of brand image on brand switching. Understanding the influence of price on brand switching. Understanding the influence of promotion on brand switching. The type of this research used explanatory research with quantitative approach. The result of the study multiple linear regression reveals that: Brand Image, Price and Promotion has influences simultaneously on Brand Switching based on the F-test value and Promotion has dominant influence based on the t-test value. Promotion reasons has significant influence on brand switching are consumer obtained the information and interesting advertising about the superiority of the product, consumer attracted with sales promotion such as free short messages service (SMS), additional internet quota and free of charge phone calls in specified time and it triggered the consumer to switch to other products. Brand image has a significant influence on Brand Switching. Price has a significant influence on Brand Switching. Promotion has a significant influence on Brand Switching. Therefore, the company is expected to improve and maintain the quality of the promotion that has big influence on Brand Switching. Key words: Brand image, Price, Promotion and Brand switchingABSTRAKHasil dari penelitian ini menunjukkan bahwa berdasarkan analisis rumus NPL Bank Sinar tahun 2011 mengalami peningkatan tiap tahunnya 2010 = 1,73%, 2011 = 1,94%, dan 2012 = 1,81%. Sementara resiko pasar dengan melihat IRR mengalami penurunan di tahun 2010 dari 0,028 % menjadi 0,022% di tahun 2011, dan meningkat di tahun 2012 menjadi 1,909%, dan Resiko likuiditas dengan menggunakan dua rasio yaitu LDR dan LAR, mengalami peningkatan dan penurunan. Hal ini menunjukkan bahwa Bank Sinar memiliki profitabilitas yang bagus terhadap pengembalian kembali dana pihak ketiga. GCG Bank Sinar juga memiliki manajemen yang sangat bagus yang terbukti dari tahun 2010 – 2012 menunjukkan predikat komposit baik dengan penentuan matriks penilaian bank sehat berdasarkan Peraturan Bank Indonesia No. 13 dan predikatnya adalah baik seluruh nilai komposit tersebut masih berada dalam aturan lebih besar atau sama dengan (≤) 1.5. Jika dilihat dari CAR, Bank Sinar berada pada peringkat 2 hal tersebut menunjukkan bahwa Bank Sinar sebagai Bank umum memiliki tingkat kesehatan yang wajar.Kata kunci : Analisis Faktor, Tingkat Kesehatan Bank, Kinerja Bank, RGEC